USM PUSHES FOR MERBOK MANGROVES TO BE GAZETTED AS A UNESCO BIOSPHERE RESERVE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 19 Oct. 2015 – A team of researchers from Universiti Sains Malaysia (USM) is actively preparing a dossier for the Merbok Mangrove Forest in Kedah to be gazetted as a UNESCO (United Nations Education, Scientific and Cultural Organisation) Biosphere Reserve.